Post Implementation Review of E-Cover Note : A Case Study in the State of Perlis - Syed Najihuddin, Syed Hassan (2005)
The aim of this study is to identify user acceptance to E-Cover Note application which is implemented by Road Transport Department. The application is an electronic service provided online for insurance companies and agencies in replacement of the manual cover notes system. This paper also describes the evolvement and emergence of e-government globally. In addition, it also identifies Technology Acceptance Model (TAM) as a methodology for evaluating user acceptance of the new information technology. A user acceptance testing was carried out in which twelve questions was asked via the questionnaire distributed among the users in the state of Perlis. The study shows that the users accept this application as useful for their work even though the learning process is quite complicated at the beginning. This project can serve as a model for future studies in evaluating user acceptance of new technologies. Further studies can be conducted to identify user acceptance of e-Cover Note in other state in Malaysia.